A clinicoradiographic comparison of the effects of platelet-rich fibrin gel and platelet-rich fibrin membrane as scaffolds in the apexification treatment of young permanent teeth - Madhu Santhakumar; Shivsankar Yayathi; N Retnakumari (Wolters Kluwer Medknow Publications, 2018)
Aims: This triple blinded clinical trial was undertaken to check whether Platelet rich firin in its membrane form is as reliable as when it is in the gel form. Settings and Design: Triple blinded randomized clinical trial. Methods and Material: 20 patients in PRF gel group and 20 patients in PRF membrane group selected after randomization and considering inclusion and exclusion criteria were taken up for this study. The samples were clinically and radiographically evaluated for success. Results and Conclusions: Regenerative endodontics with PRF membrane is easier and less time consuming. They have similar clinical success.PRF gel gave a better radiographic success in 12 months period.